Activation of the NLRP3 inflammasome by islet amyloid polypeptide provides a mechanism for enhanced IL-1ß 2 in type 2 diabetes - Masters, S.; Dunne, A.; Subramanian, S.; Hull, R.; Tannahill, G.; Sharp, F.; Becker, C.; Franchi, L.; Yoshihara, E.; Chen, Z.; Mullooly, N.; Mielke, L.; et al. (Nature Publishing Group, 2010)
Interleukin 1ß 2 (IL-1ß 2) is an important inflammatory mediator of type 2 diabetes. Here we show that oligomers of islet amyloid polypeptide (IAPP), a protein that forms amyloid deposits in the pancreas during type 2 diabetes, triggered the NLRP3 inflammasome and generated mature IL-1ß 2. One therapy for type 2 diabetes, glyburide, suppressed IAPP-mediated IL-1ß 2 production in vitro. Processing of IL-1ß 2 initiated by IAPP first required priming, a process that involved glucose metabolism and was facilitated by minimally oxidized low-density lipoprotein. Finally, mice transgenic for human IAPP had more IL-1ß 2 in pancreatic islets, which localized together with amyloid and macrophages. Our findings identify previously unknown mechanisms in the pathogenesis of type 2 diabetes and treatment of pathology caused by IAPP.